Analyzing and Investigating the Legal Aspects of Green Policy - Novianti, Dwi (Enigma Institute, 2023)
The legal dimensions of green policy are crucial in propelling tangible transformation towards sustainable development. Gaining insights from other viewpoints, including those from the public, commercial, administrative, and international sectors, can facilitate the development and execution of policies that are both effective and comprehensive. Green policy is incorporated into the environmental legal system from a public law standpoint, with the aim of ensuring justice and safeguarding the environment against harm. Private law serves as a strong defense for the human rights of residents to reside in a clean and safe environment, achieved through the use of legal agreements and legal actions. From an administrative law perspective, green policy is regarded as a mechanism that governs and oversees government actions, ensuring their alignment with ecologically sustainable ideals. Indonesia must fulfill its commitments in global agreements such as the United Nations Framework Convention on Climate Change (UNFCCC) and the Paris Agreement, which also possess legal standing at the international level.